(untitled) (Economics and region, 2021)
The aim of the article is to study the problems and identify priority areas for improving the level of financial literacy of the population during the active development of digital technologies of the financial market in Ukraine. It is argued that financial literacy is one of the main tools for overcoming poverty and a driver of economic prosperity, as society can achieve economic success only when citizens have the skills to make responsible and informed decisions in the financial sphere and are able to shape their own well-being. A financially conscious society is one of the most important factors in the country’s economic growth, investment activity and rising incomes. The issue of financial literacy has become more relevant in recent years, when the problems of economic instability and crisis related to the world pandemic, war and the need for reconstruction in the post war period have become much more acute. Digital technologies in all spheres of human activity, especially in the financial sphere and in the market of educational services, are also an important driver of financial literacy. This problem is relevant because the ability to properly and rationally manage personal finances and business finances is becoming an urgent need for citizens. World Bank data show that financial literacy strategies have been approved in 44 countries, and similar strategic measures are being developed in 27 countries. The article analyzes and summarizes financial literacy programs implemented in Australia, the United Kingdom, the United States and China. Analysis of world experience in improving the financial literacy of the population shows that developed countries support and finance measures to increase the level of financial literacy of the population. It is proved that in Ukraine the level of financial literacy of the population is rather low. After all, according to the study, during the 30 years of market relations in Ukraine, no one systematically engaged in financial education of the population, which independently gained some knowledge of their own mistakes and losses from unscrupulous banks and other financial institutions, failed investments and more. The National Bank of Ukraine is taking measures to increase the level of financial literacy. However, the development of fintech requires an adequate level of financial literacy of users of these services. Measures to increase the level of financial literacy of Ukrainians are proposed.